2020
DOI: 10.3389/fmars.2020.00135
|View full text |Cite
|
Sign up to set email alerts
|

Protistal Grazers Increase Grazing on Unicellular Cyanobacteria Diazotroph at Night

Abstract: In this study, we have for the first time analyzed diel microzooplankton grazing selectivity on unicellular cyanobacterial diazotroph (i.e., Crocosphaera watsonii WH8501) and nondiazotrophic unicellular microalga (i.e., Chlorella autotrophica). A mixed diet consisting of these two phytoplankton was supplied to four species of protistal grazers during daytime and nighttime, respectively. C. watsonii fixes nitrogen during nighttime and showed a stronger diel pattern of cellular C:N ratio than C. autotrophica. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…The potential grazers of Crocosphaera shown in Fig. 5 represent a large diversity of secondary producers, dominated by genera of dinoflagellates and ciliates known to graze on the numerically dominant cyanobacteria genera, Prochlorococcus and Synechococcus in the NPSG (Frias-Lopez et al 2009), and representatives recently confirmed to also feed on Crocosphaera in culture (Deng et al 2020). These grazers include numerous prymnesiophytes, nanoflagellates like Metromonas, ciliates like Uronema or Strobilidium, and dinoflagellates like Table 2 Grazing parameterization estimated by linear mixed-effect regression (Eq.…”
Section: Mesoscale Variability Of Crocosphaera and Associated Grazersmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential grazers of Crocosphaera shown in Fig. 5 represent a large diversity of secondary producers, dominated by genera of dinoflagellates and ciliates known to graze on the numerically dominant cyanobacteria genera, Prochlorococcus and Synechococcus in the NPSG (Frias-Lopez et al 2009), and representatives recently confirmed to also feed on Crocosphaera in culture (Deng et al 2020). These grazers include numerous prymnesiophytes, nanoflagellates like Metromonas, ciliates like Uronema or Strobilidium, and dinoflagellates like Table 2 Grazing parameterization estimated by linear mixed-effect regression (Eq.…”
Section: Mesoscale Variability Of Crocosphaera and Associated Grazersmentioning
confidence: 99%
“…In this size range, there is a diverse consortium of unicellular eukaryotes (protists) that consume phytoplankton via strict heterotrophy or mixotrophy. The assemblage is generally dominated in biomass by dinoflagellates, ciliates, or rhizaria (Pasulka et al 2013), which specifically prey on cyanobacteria (Vors et al 1995; Hartmann et al 2012; Deng et al 2020). Most of the organic matter assimilated by grazers is likely remineralized since only 2–17% (5.6% on average) of the C fixed by photosynthesis is eventually exported from the euphotic layer (Karl et al 1996).…”
mentioning
confidence: 99%
“…Some studies have suggested that grazing pressure on picoplanktonic prey by nano planktonic (2−20 μm) protistan consumers is highest at night because the probability of encountering prey increases due to the presence of newly divided cyanobacterial cells (Christaki et al 2002, Tsai et al 2009. Alternatively, Deng et al (2020) reported higher grazing rates during the night for the heterotrophic dinoflagellate Oxyrrhis marina preying on the cyanobacterium Crochosphaera watsonii, a result they attributed to improved nutritional qual-ity of the prey as a result of nighttime nitrogen fixation. Other studies have reported higher grazing pressure during the day, citing preferential grazing on small, post-division cells early in the day (Dolan & Simek 1999) or compensatory feeding on low quality prey (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…size, ecto/endosymbiosis) are important factors influencing prey selectivity. As reviewed in Kirchman (2012), protistan grazing is primarily size-selective, but laboratory studies have suggested that grazing on diazotrophs also depends on the timing of N 2 fixation as a consequence of diel changes in C:N stoichiometry altering the nutritional quality of prey (Deng et al 2020). Since Crocosphaera and the vegetative cells of Calothrix have relatively small sizes, low C:N ratios (Table 2), and can be found at high concentrations during the summer (Fig.…”
Section: Resultsmentioning
confidence: 99%